Exercise program to reduce the risk of cognitive decline and physical frailty in older adults: study protocol for an open label double-arm clinical trial - Noguchi-Shinohara, Moeko; Yokoyama, Kunihiko; Komatsu, Junji; Masuda, Kazumi; Kouno, Mitsunobu; Yoshita, Mitsuhiro; Ono, Kenjiro (Frontiers in Aging Neuroscience, 2023)
Objective It is a big problem that many older adults are physically inactive. Well-known benefits of physical exercise include a decrease in the risk of cognitive decline and physical frailty. Therefore, this study aims to examine whether our proposed exercise program can prevent cognitive decline and improve physical function in the elderly. Methods This study will include nondemented older adults (n = 160) without regular exercise habits. The trial will include a physical exercise training program (once a week) and nutritional lectures (once a month) over 5 months and follow-up for ≥1 year. The primary endpoint is the program’s efficacy in preventing cognitive decline, as assessed by changes in the memory performance index of the mild cognitive impairment (MCI) screen; the secondary endpoints are the incidence of MCI and dementia, physical testing, and frailty proportion. In the exploratory phase of the study, we will elucidate the underlying diseases causing MCI in community-dwelling older adults by neuroimaging. Discussion This double-arm trial that aims to assess the impact of physical exercise on nondemented older adults’ cognitive and physical function. Furthermore, our newly developed exercise program will be easy for older adults to undertake. Clinical Trial Registration: https://clinicaltrials.gov/, identifier [jRCT 1040220140].